2021
DOI: 10.3389/fsoc.2021.614713
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patterns of Economic Insecurity for Post-Soviet Migrant Women in Europe

Abstract: This study deals with meanings of economic insecurity for post-Soviet migrant women in Germany, Italy, and Spain, elaborating on its cultural underpinnings. Drawing upon several data sources, including interviews, observation, and online data, as well as judicial material, this study addresses the ways women from the former Soviet Union experience economic insecurity and which strategies they develop to cope. We consider women's age, social background, and level of education, analyzing their embeddedness into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The status of an outsider borders on invisibility (Mählck, 2013), which makes migrant women representatives of "marginalised elites" (Riaño, 2016). This significantly echoes the overall position of post-Soviet migrant women in the German socio-economic structure: while in educational terms many of them are equipped with good qualifications, they are unevenly represented in highly skilled positions within the German labor market (Färber et al, 2008;Gewinner and Salvino, 2021;Kogan, 2012). This raises the question: how do women migrants perceive discrimination in academia and what are the instances they deal with in German research organizations?…”
Section: Current State Of Research On Discrimination Of (Highly) Skil...mentioning
confidence: 99%
See 2 more Smart Citations
“…The status of an outsider borders on invisibility (Mählck, 2013), which makes migrant women representatives of "marginalised elites" (Riaño, 2016). This significantly echoes the overall position of post-Soviet migrant women in the German socio-economic structure: while in educational terms many of them are equipped with good qualifications, they are unevenly represented in highly skilled positions within the German labor market (Färber et al, 2008;Gewinner and Salvino, 2021;Kogan, 2012). This raises the question: how do women migrants perceive discrimination in academia and what are the instances they deal with in German research organizations?…”
Section: Current State Of Research On Discrimination Of (Highly) Skil...mentioning
confidence: 99%
“…Women are not merely driven by the aspiration for career advancement, but much more by their culturally rooted family values, such as motherhood and harmonic family relationships. Previous research found that highly skilled post-Soviet women placed equal importance on both paid employment and family, which greatly predetermines the modes of their employment and family choices (Gewinner and Salvino, 2021), and as a consequence, of their life satisfaction.…”
Section: Highly Skilled Post-soviet Women Migrants In German Academiamentioning
confidence: 99%
See 1 more Smart Citation